Base-Promoted Reactions of Hydroxyquinones with Pyrones: A Direct and Sustainable Entry to Anthraquinones and Naphthoquinones - Yu, Huangchao; Kraus, George A. (Synlett, 2019)
Hydroxybenzoquinones and hydroxynaphthoquinones react with methyl coumalate and 5-cyanopyrone to generate anthraquinones and naphthoquinones in good to excellent yields.
Keywords: anthraquinone; naphthoquinone; pyrone; base-promoted; synthesis